Comparison of endoscopic submucosal resection with ligation and endoscopic submucosal dissection for small rectal neuroendocrine tumors: A multicenter retrospective study - Kenshi Matsuno; Hideaki Miyamoto; Hideki Kitada; Shinichi Yoshimatsu; Fumio Tamura; Kouichi Sakurai; Kotaro Fukubayashi; Takashi Shono; Hiroko Setoyama; Taichi Matsuyama; Shinichiro Suko; Rei Narita; et al. (DEN Open)
Abstract Objectives Endoscopic submucosal resection with band ligation (ESMR‐L) and endoscopic submucosal dissection (ESD) are both standard endoscopic resection methods for rectal neuroendocrine tumors (NETs) <10 mm in size. However, there is no definitive consensus on which is better. Here, we compared the efficacy of ESMR‐L and ESD for small rectal NETs. Methods This was a multicenter retrospective cohort study including 205 patients with rectal NETs who underwent ESMR‐L or ESD. Treatment outcomes were compared by univariate analysis, multivariate analysis, and inverse probability treatment weighting (IPTW) using propensity scores. Subgroup analysis evaluated the impact of the endoscopist's experience on the technical outcome. Results Eighty‐nine patients were treated by ESMR‐L and 116 by ESD. The R0 resection rate was not significantly different between the two (90% vs. 92%, p = 0.73). The procedure time of ESMR‐L was significantly shorter than for ESD (17 min vs. 52 min, p < 0.01) and the hospitalization period was also significantly shorter (3 days vs. 5 days, p < 0.01). These results were confirmed by multivariate analysis and also after IPTW adjustment. The procedure time of ESD was significantly prolonged by a less‐experienced endoscopist (49 min vs. 70 min, p = 0.02), but that of ESMR‐L was not affected (17 min vs. 17 min, p = 0.27). Conclusions For small rectal NETs, both ESMR‐L and ESD showed similar high complete resection rates. However, considering the shorter procedure time and shorter hospitalization period, ESMR‐L is the more efficient treatment method, especially for less‐experienced endoscopists.